ICON DESIGN OF SURABAYA HISTORICAL BUILDING - Satrya Dirgantara (Universitas Bunda Mulia, 2021)
Surabaya is a large city that is developing, there are often developments in the construction of buildings and places that aim to improve the economy. Although Surabaya is known as a metropolitan city, the city of Surabaya has many relics of colonial-era cultural heritage, many buildings – historic buildings of Dutch colonial heritage are still sturdy and magnificent to this day. This study raised 5 historic buildings in the city of Surabaya to be designed in the form of icons. The buildings include Heroes Monument, Surabaya Youth Hall, Surabaya City Hall, De Javasche Bank, and Kebonrojo Post Office. The goal is to implement this historic building in the form of an iconic vector. The function of this design is to spread the symbol of the historic buildings in the city of Surabaya. Design is done through data collection in the form of observation, documentation, and literature studies. Through this design, the historic building in Surabaya can be implemented as an iconic vector.